Technology Challenge: EFL Teacher Experience Teaching Online at Kindergarten - Na'imah; Muassomah; Azizah Nurul Fadlilah (Universitas Pendidikan Ganesha, 2022)
The application of learning technology makes a severe challenge for the English teachers as a foreign language (EFL) at Kindergarten learning online, which results in neglected outcomes. Various kinds of the latest tools and appropriate online learning technology are widely available, but the limited ability of EFL teachers and students can't keep up with the progress. This study aims to analyses how the challenges of EFL teachers and students using online learning technology impact output quality in kindergartens. The data for this study were sourced from the owners of the Kindergarten, the principal, and 12 EFL teachers who had considerable experience in two private Kindergartens. Data collection is done through observation, documentation, and interview. Data analysis is manually inductive with model producer which started from data collection, reduction, data display, and verification. The study results show that the importance of appropriate technology that EFL teachers and students cannot use has resulted in a fall in the quality of outcomes that have a global impact. The impact of children's education in Kindergarten affects further formal education, which should follow the demands of the development of science and technology in the present and the future. This condition does not pursue the educational vision, mission, and goals. At the same time, this study requires problem-solving based on problem-based learning, and excellent teachers must master Technological Pedagogical and Content Knowledge (TPACK).